Proton transfer reactions in the red light-activatable channelrhodopsin variant ReaChR and their relevance for its function - Kaufmann, Joel C. D. (J Biol Chem, 2017)
Channelrhodopsins (ChRs) are light-gated ion channels widely used for activating selected cells in large cellular networks. ChR variants with a red-shifted absorption maximum, such as the modified Volvox carteri ChR1 red-activatable channelrhodopsin (“ReaChR,” λ(max) = 527 nm), are of particular interest because longer wavelengths allow optical excitation of cells in deeper layers of organic tissue. In all ChRs investigated so far, proton transfer reactions and hydrogen bond changes are crucial for the formation of the ion-conducting pore and the selectivity for protons versus cations, such as Na(+), K(+), and Ca(2+) (1). By using a combination of electrophysiological measurements and UV-visible and FTIR spectroscopy, we characterized the proton transfer events in the photocycle of ReaChR and describe their relevance for its function. 1) The central gate residue Glu(130) (Glu(90) in Chlamydomonas reinhardtii (Cr) ChR2) (i) undergoes a hydrogen bond change in D → K transition and (ii) deprotonates in K → M transition. Its negative charge in the open state is decisive for proton selectivity. 2) The counter-ion Asp(293) (Asp(253) in CrChR2) receives the retinal Schiff base proton during M-state formation. Starting from M, a photocycle branching occurs involving (i) a direct M → D transition and (ii) formation of late photointermediates N and O. 3) The DC pair residue Asp(196) (Asp(156) in CrChR2) deprotonates in N → O transition. Interestingly, the D196N mutation increases 15-syn-retinal at the expense of 15-anti, which is the predominant isomer in the wild type, and abolishes the peak current in electrophysiological measurements. This suggests that the peak current is formed by 15-anti species, whereas 15-syn species contribute only to the stationary current.